EFEKTIVITAS BIMBINGAN PRANIKAH DALAM MEWUJUDKAN KELUARGA SAKINAH OLEH KANTOR URUSAN AGAMA (KUA) MAYAMUK KABUPATEN SORONG - Umrah, St; Kartika, Dewi (Muadalah : Jurnal Hukum, 2024)
The occurrence of marital conflict is often because the marriage is not in accordance with the expectations and goals of the couple who marry. This is due to several things, for example, the bride and groom do not understand the real purpose of marriage even though the marriage is based on mutual love. In order to build a peaceful family, pre-marital guidance is needed, which is an effort to provide assistance to couples in solving problems or information about marriage, which will be faced by prospective brides. The focus of the problem studied are: 1) how is the implementation of premarital guidance program in KUA Mayamuk Sorong Regency? 2) how is the effectiveness of premarital guidance in forming a sakinah family after marriage at KUA Mayamuk Sorong Regency? Based on the sakinah of the researcher's interviews with the three couples who have participated in premarital guidance and have been married, the data obtained has shown that some of these informants have met the benchmarks of a Sakinah family (sakinah i family). Sakinah i families are families that are built on a legal marriage and have been able to fulfill their spiritual and material needs minimally but still cannot fulfill their social psychological needs, such as educational needs, religious guidance and family, following religious social interactions with their environment.